Wafer-Scale Organic Complementary Inverters Fabricated with Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Sarcletti, Marco; Zhao, Yuhan; Rejek, Tobias; Liu, Xinxin; Park, Hyoungwon; Strohriegl, Peter; Halik, Marcus (Advanced Electronic Materials, 2020)
Self-assembled monolayers (SAMs) of π-conjugated molecules can achieve robust charge transport by the formation of ordered 2D layers at the desired regions, which enable their application for organic integrated circuits. Here, the self-assembled monolayer field-effect transistor concept is applied as a scalable method to realize fully integrated complementary inverters by stepwise semiconductor deposition. Two-component stacked bilayer ambipolar transistors are fabricated by semiconducting self-assembled monolayers (n-SAM or p-SAM) as the bottom layer and a complementary thin-film semiconductor layer on top. The integrated complementary metal-oxide-semiconductor like (CMOS-like) inverter achieves proper logic performances. The nanometer-thin monolayers exhibit effective charge transport and their flat, homogeneous surfaces benefit the interconnected growth of the top layer. Furthermore, by controlling the solution-based and region-selective deposition of p- and n-type SAMs, fully integrated CMOS inverters are realized on wafer scale by photolithography for the first time. The CMOS inverters show a nearly 100% yield with a gain up to 48, and noise margin 3.68 V (73.6% of VDD/2). The strategy of semiconducting SAMs for digital logic gates demonstrates a reliable approach for sophisticated large-area circuits.
CRIS-Team Scopus Importer:2020-08-14
Keywords: organic complementary metal-oxide-semiconductor inverters; organic field-effect transistors; p-n heterojunction structures; self-assembled monolayers